CHROMNIUM PICLONAT EFFECTS IN DIET OF MALE RABBITS EXPOSED TO HEAT STRESS ON SOME PRODUCTIVE TRAITS AND BLOOD SERUM PARAMETERS - & Al-Saadi, Hashem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
current study was conducted to determine the effects of Chromium piclonat supplementation on some productive traits and serum parameters of male rabbit exposed to heat stress by used electric heaters ,twenty four male rabbits were randomly divided into four groups 6 for each, first group put in normal suitable climate condition based diet without additional Chromium and kept as positive control group , while The other three groups exposed to heat stress , the basal diet was consisted of 0, 300 , and 500 ppb of Chromium piclonate respectively as a feed additives . All rabbit received feed and water ad libitum, the results showed that there were Increasing organic Cr supplementation 300 and 500 pbb of two treated groups resulted in an increase in body weight compared with negative and positive control group , the serum glucose and cortisone hormone concentrations of both treated groups were decrease, as dietary Cr level increased (P<0.05), but Cr supplementation did not affect total protein, albumen and globulin. These data indicated that organic Cr supplementation increased some performance traits, particularly body weight production and decreased in glucose and cortisone hormone while there were not significant effect in the total of serum protein, Albumin and globulin ,it can be concluded that adding chromium piclonat in dose 300,500pbb in diet of rabbits during hot periods has a benefits to overcome deterioration in some performance traits related to oxidative stress results from heat stress.